(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the basic information about the methodology for the development of the design competency of future drawing science teachers in the new generation of AutoCAD graphics software is provided. It was written on the basis of the results of research carried out by pedagogical scientists on the development of spatial imagination and thinking of future teachers, as well as design competence.